Uracil restores susceptibility of methicillin-resistant Staphylococcus aureus to aminoglycosides through metabolic reprogramming - Fan, Lvyuan; Pan, Zhiyu; Liao, Xu; Zhong, Yilin; Guo, Juan; Pang, Rui; Chen, Xinhai; Ye, Guozhu; Su, Yubin (Frontiers in Pharmacology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is highly resistant to most antibiotics, and quickly becoming a significant public health burden. Although there have been several studies investigating the resistance mechanisms in MRSA, treatment strategies are still lacking. In the present study, we found that uracil could synergize with aminoglycosides to kill MRSA (USA300). Reprogramming metabolomics displayed uracil reprogrammed bacterial metabolism, especially enhanced the tricarboxylic acid (TCA) cycle to elevate NADH production and proton motive force, thereby promoting the uptake of antibiotics. Furthermore, uracil increased cellular respiration and ATP production, resulting the generation of reactive oxygen species (ROS). Thus, the combined activity of uracil and antibiotics induced bacterial death. Inhibition of the TCA cycle or ROS production could attenuate bactericidal efficiency. Moreover, uracil exhibited bactericidal activity in cooperation with aminoglycosides against other pathogenic bacteria. In a mouse mode of MRSA infection, the combination of gentamicin and uracil increased the survival rate of infected mice. Our results suggest that uracil enhances the activity of bactericidal antibiotics to kill Gram-positive bacteria by modulating bacterial metabolism. This study provides a novel strategy to tackle intractable MRSA infections.